AV delay optimisation in LV only CRT: constant fusion pacing is easier in patients with first degree AV block. (25th November 2020) - Vacarescu, C; Luca, C.T; Petrescu, L; Ionac, A; Mornos, C; Goanta, E.V; Crisan, S; Lazar, M.A; Cozma, D
Abstract: Background: LV only pacing is non-inferior to BiV pacing, and recent publications showed that DDD CRT without RV lead is safe in patients with normal atrioventricular (AV) conduction, although there are no device algorithms available for fusion pacing and PR interval variability is understudied in this population. Purpose: To analyse AV behaviour in patients with DDD CRT and the impact to effective fusion maintenance. Methods: Consecutive patients with right atrium/left ventricle leads DDD CRT pacing system were included. Prospective data were collected at every 6 months follow-up visits: device interrogation, exercise test (ET), echocardiography. CRT assessment during ET analysed loss of LV capture with special focus on maintaining constant fusion pacing during exercise. We defined 2 groups of patients: longer PR interval patients (200–250 ms) and normal PR interval patients (<200 ms). In case of LV loss of capture or unsatisfactory LV fusion pacing, device reprogramming was performed individualised for each patient and BB/ivabradine dose titration was done to achieve stability of PR spontaneous interval. Patients were rescheduled in no later one month to be reassessed by ET. Results: 55 patients (29 male) aged 62±11 y.o. were included, 36 patients with normal PR and 19 patients with longer PR. During follow-up (45±19 months), a total of 235 ETs were performed with mean exercise load 118±35 watts. In the normal PR group, 14 patients (39%) had inadequate pacing or loss of LV capture during ET due to physiological shortening of PR interval vs. 4 patients (21%) in the longer PR group. Loss of LV capture by exceeding maximum tracking rate (MTR) was noted in 6 patients (17%) with normal PR vs. 2 patients (11%) with long PR. Post ET device optimisation included: reprogramming rate adaptive AV interval (23±8 ms decrease in normal PR patients vs. 12±7 ms in longer PR patients, p<0.0001) and individualised programming of MTR. BB/ivabradine optimisation was performed in 32% of patients with normal PR vs. 13% of patients with longer PR. Conclusions: A lower rate of optimisations after ET was needed in patients with a slightly longer AV conduction to achieve stability of fusion pacing DDD CRT, without device algorithms. Larger studies are needed to assess AV conduction variability and the benefits of fusion pacing CRT in patients with longer PR interval. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): University of Medicine and Pharmacy "Victor Babes", Timisoara; Timisoara Institute of Cardiovascular Diseases